Monte Carlo simulation for the estimation of the glandular breast dose for a digital breast tomosynthesis system. Issue 4 (4th December 2014) - Rodrigues, Leonardo; Magalhaes, Luis Alexandre Goncalves; Braz, Delson
Abstract: Digital breast tomosynthesis (DBT) is a screening and diagnostic modality that acquires images of the breast at multiple angles during a short scan. The Selenia Dimensions (Hologic, Bedford, Mass) DBT system can perform both full-field digital mammography and DBT. The system acquires 15 projections over a 15° angular range (from −7.5° to +7.5°). An important factor in determining the optimal imaging technique for breast tomosynthesis is the radiation dose. In breast imaging, the radiation dose of concern is that deposited in the glandular tissue of the breast because this is the tissue that has a risk of developing cancer. The concept of the normalised mean glandular dose ( D g N) has been introduced as the metric for the dose in breast imaging. The D g N is difficult to measure. The Monte Carlo techniques offer an alternative method for a realistic estimation of the radiation dose. The purpose of this work was to use the Monte Carlo code MCNPX technique to generate monoenergetic glandular dose data for estimating the breast tissue dose in tomosynthesis for arbitrary spectra as well as to observe the deposited radiation dose by projection on the glandular portion of the breast in a Selenia Dimensions DBT system. A Monte Carlo simulation of the system was developed to compute the D g N in a craniocaudal view. Monoenergetic X-ray beams from 10 to 49 keV in 1-keV increments were used. The simulation utilised the assumption of a homogeneous breast composition and three compositions (0 % glandular, 50 % glandular and 100 % glandular). The glandular and adipose tissue compositions were specified according ICRU Report 44. A skin layer of 4 mm was assumed to encapsulate the breast on all surfaces. The breast size was varied using the chest wall-to-nipple distance (CND) and compressed breast thickness ( t ). In this work, the authors assumed a CND of 5 cm and the thicknesses ranged from 2 to 8 cm, in steps of 2 cm. The fractional energy absorption increases (up to 44.35 % between 0 % glandular and 100 % glandular) with the increase in the glandular fraction due to changing the composition and increasing the density. Low-energy photon absorption occurred in the first tissue layer. The D g N decreases with increasing the compressed breast thickness. The graphs show that between 15 and 30 keV provides the greatest contribution to the dose and that the glandular dose is almost constant as a function of the projection angle. The results may be useful for optimising tomosynthesis procedures and evaluating the dose distribution in the projections in a craniocaudal view.